Scientific opinion on the safety and efficacy of AGal-Pro (alpha-galactosidase and endo-1,4-beta-glucanase) as a feed additive for chickens reared for laying and minor poultry species for fattening - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (EFSA Journal, 2013)
The additive AGal-Pro, also named as Biogalactosidase BL and AlphaGal BL, is a preparation of alpha-galactosidase (galactosidase) produced by a genetically modified strain of Saccharomyces cerevisiae and of endo-1,4-beta-glucanase (glucanase) produced by a non-genetically modified strain of Aspergillus niger. This product is authorised for use in chickens for fattening as a zootechnical additive, functional group of digestibility enhancers. The applicant seeks for the extension of the use of the additive to chickens reared for laying and to minor poultry species for fattening at a dose range of 50 to 100 alpha-galactosidase units and of 285 to 570 glucanase units per kg feed (corresponding to 50 to 100 mg additive/kg feed). In a previous evaluation the additive was shown to be safe in chickens for fattening at a dose of 100 galactosidase and 570 glucanase units per kg feed. The FEEDAP Panel considers that this conclusion can be extended to chickens reared for laying. Given the margin of safety established for the major species, these conclusions can be extrapolated to minor poultry species for fattening. The potential of the product to be efficacious when used in chickens for fattening was previously established at the dose of  50 U galactosidase and 285 U glucanase per kg feed. The FEEDAP Panel considers that this conclusion applies to chickens reared for laying. Since the mode of action of the galactosidase and glucanase can be reasonably assumed to be the same in all poultry species the conclusion on efficacy in chickens for fattening can be extrapolated to include the minor poultry species for fattening.